Germantown : a military history of the Battle for Philadelphia, October 4, 1777 - Harris, Michael C., 1978- (Savas Beatie, LLC, 2020)
"On October 4, 1777, the Battle of Germantown represented George Washington's attempt to recapture Philadelphia. Obscured by darkness and a morning fog, Washington launched a surprise attack on the British garrison at Germantown. His attack found initial success and drove the British legions before him. The recapture of the colonial capital seemed within Washington's grasp until poor decisions by the American high command brought about a reversal of fortune and a British victory"--